Introduction to organic laboratory techniques - Donald L. Pavia (Thomson Brooks/Cole, 2005)
In this laboratory textbook for students of organic chemistry, experiments are designed to utilize standard-scale ("macroscale") glassware and equipment but with smaller amounts of chemicals and reagents. The textbook features a large number of traditional organic reactions and syntheses, as well as the isolation of natural products and experiments with a biological or health science focus. The organization of the text is based on essays and topics of current interest. There are six introductory technique-based experiments and eleven project-based experiments. In addition, there is a section of green chemistry experiments. The book contains a comprehensive treatment of laboratory techniques, including small-scale and some microscale methods